Effect of Feeding of Hydroponics Maize Green Fodder with and without Supplementation of Probiotics (Saccharomyces cerevisiae) on Feed Consumption in Gir Calves - Joshi, Monika; Sharma, S. K.; Vaishnava, C. S. (Indian Journal of Animal Nutrition, 2020)
Present investigation was undertaken to determine the chemical composition and assessment of feed consumption of hydroponics maize fodder with and without supplementation of probiotic (Saccharomyces cerevisiae) in Gir calves. Total 36 male Gir calves of almost same age group were distributed equally by completely randomized block design in nine groups. Calves in group T1 were treated as control and were fed basal feed and concentrate mixture as per requirement. For calves in T2, T3, T4 and T5 groups, 25%, 50%, 75% and 100% of crude protein (CP) supplied through concentrate mixture was replaced by hydroponics maize fodder, respectively, whereas in T6, T7, T8 and T9 groups, 25% 50%, 75% and 100% of CP supplied through concentrate mixture was replaced by hydroponics maize fodder alongwith probiotics (Saccharomyces cerevisae), respectively. The results indicated that hydroponics maize fodder had shown good nutrient profile such as crude protein, ether extract and nitrogen free extract in present experiment whereas yeast was found to be richer source of calcium and phosphorus. There was highly significant effect (P